2012 IEEE Fifth International Conference on Cloud Computing 2012
DOI: 10.1109/cloud.2012.22
|View full text |Cite
|
Sign up to set email alerts
|

F2Box: Cloudifying F2F Storage Systems with High Availability Correlation

Abstract: The increasing popularity of Cloud storage services is leading end-users to store their digital lives (including photos, videos, work documents, etc.) in the Cloud. However, many users are still reluctant to move their data to the Cloud due to the amount of control ceded to Cloud vendors. To let users retain the control over their data, Friend-to-Friend (F2F) storage systems have been presented in the literature as a promising alternative.However, as we show in this paper, pure F2F storage systems present a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Only Eq. (11) in Case 1 should be rederived, because ‫ݐ‬ ௨௧ ௨ is known if the user is offline at time ‫,ݐ‬ i.e., ‫ݐ‬ ௨௧ ௨ is a constant. Therefore ‫ݓݐ‬ ௨_ ‫ݐ(‬ ᇱ ) should be calculated using Eq.…”
Section: B Predicting ‫ܦ‬mentioning
confidence: 98%
See 3 more Smart Citations
“…Only Eq. (11) in Case 1 should be rederived, because ‫ݐ‬ ௨௧ ௨ is known if the user is offline at time ‫,ݐ‬ i.e., ‫ݐ‬ ௨௧ ௨ is a constant. Therefore ‫ݓݐ‬ ௨_ ‫ݐ(‬ ᇱ ) should be calculated using Eq.…”
Section: B Predicting ‫ܦ‬mentioning
confidence: 98%
“…In 2012, Gracia-Tinedo et al [11] showed that pure F2F storage systems present a poor QoS, mainly due to the availability correlations, and proposed a hybrid architecture called F2Box to combine F2F storage systems and the cloud storage services. F2Box uses erasure coding to replicate the data and allow users to adjust the amount of redundancy according to the availability patterns exhibited by friends.…”
Section: Cloud-assisted P2p Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…The idea of using a cloud infrastructure to boost performance of P2P is not new. Cloud helpers are proposed in [17] to increase availability in a friendto-friend (F2F) backup system. This is similar to our work in that F2F systems are also based on social overlays, and that data is also confined to ego networks.…”
Section: Related Workmentioning
confidence: 99%